Suspended sediment and phosphorus budget and trophic status of Bukit Merah Reservoir, Perak, Malaysia - Najib, Sumayyah Aimi Mohd; Ismail, Wan Ruslan; Omar, Mohamad Adam (Journal of Environmental Geography, 2017)
Bukit Merah Reservoir (BMR) is one of the 51 impoundments in Malaysia. BMR is the oldest reservoir built in the early 1900s originally to store water for irrigation, but nowadays its functions include also flood control and water supply. Nowadays, it is threatened by land use change in the upper catchments and surrounding activities, which feeding eroded material and chemicals into the reservoir. Suspended sediment, as well as, nutrient fluxes into BMR are becoming an increasing threat to the reservoir, as its sedimentation and eutrophication accelerate. This paper discusses our study on the BMR carried out between March 2008 and April 2009 to assess the water quality status, and to determine the sediment and Total Phosphorus (TP) influx into the south pool lake. An estimated amount of suspended sediment fluxes of about 2,900 t year−1 came from the north pool lake (18%) and 12,900 t year−1 from the main Kurau River inlet (82% of the total input to the BMR). Of these total sediment input (nearly 15,800 t) about 5,600 t (36%) of the total sediment influx was trapped in the BMR. TP influx was about 18.8 t year−1 and about 7 t (37%) was trapped in the reservoir. The amount sediment and TP stored in the BMR affect the water quality of the lake, therefore the mean trophic state of the lake is eutrophic (TSI of 54.4) related to high productivity. Increasing sediment input into the reservoir has affected the reservoir volume and frequent flooding down-stream of the reservoir during rainy seasons, while eutrophication has caused the lake water quality deterioration.